THE ROLE OF EMULATING ROLE MODELS IN ENHANCING FAMILY VALUES RELIGIOUSLY IN THE LIGHT OF HOLY QURAN AND SUNNAH - Zainab Youssif Nassir; Tahir Al-Gharabawi (Galaxy International Interdisciplinary Research Journal, 2023)
The family is the small component of the large family, which is society, and therefore family cohesion is a very important part of social interaction, and this social interaction generates a state of worship of God Almighty, and we have seen in the Holy Qur’an and in many of the biographies of the prophets that the prophets used to call on God. May God Almighty grant them children to worship God Almighty. If the father is a successful leader of the family he is in, then his children will be like him, worshiping God Almighty with everything they have been taught. We must imitate all the prophets, may God’s prayers be upon them, and do what they used to do, and we pray to God to May He grant us good offspring, and may we raise our children to fear God Almighty, to worship Him, and to all the good qualities and morals that we found in him from God’s messengers and prophets. The work plan included dividing the research into an introduction, three sections, and a conclusion. The first section included the family’s interconnectedness in calling on God for its provision. The second section included the family’s interconnectedness leading to the family’s call to establish Sharia, while the third section included following the example of the prophets in their family interconnectedness leading to the worship of God and keeping away from immorality.